Huge adult cystic hygroma: anaesthesia challenge - Chabaria, Rachana (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2015)
Cystic hygroma is a rare lymphatic tumor, uncommonly seen in adults. We report a case of woman aged 55 years, who presented with a huge cystic swelling causing difficulty in neck movements. Huge neck swelling distorting the anatomy poses a challenge for securing the airway. The airway was secured with orotracheal intubation with help of a bougie after general anaesthesia, shifting the swelling off the midline by an experienced anaesthesiologist. Appropriate preoperative airway assessment, meticulous planning anticipating difficulty and simple manoeuvres, can ease intubation.